(untitled) (Theatrum historiae, 2019)
The main goal of the study is to describe the phenomena of violence of emotional nature, both in parallel and subordinate relations, in the Saxon times. Various structures of dependencies affected all areas of social life in the First Polish-Lithuanian Commonwealth. The Saxon times, coming under the reign of two Saxon electors chosen for the kings of Poland ‒ Augustus II (died 1733) and his son Fryderyk August III (died 1763), is an interesting period of decline of baroque customs and culture that began to transform under the influence of the Enlightenment ideas of the mid-18th century. From the perspective of emotions, analysis of correspondence of this period brings interesting information about social structures, dependencies and forms of psychological violence arising at this level. In the article, the phenomena of emotional violence is put under analysis to find out whether and how the used means of emotional pressure influenced the form of social relations and political life.